Opportunities and challenges in the age of COVID-19: comparing virtual approaches with circles in schools and communities - Velez, Gabriel (Comparative restorative justice, 2021)
In recent years, academics, practitioners, and activists have expanded implementation and evaluation of restorative justice in schools and justice systems. Almost exclusively, however, this implementation has involved face-to-face interaction. Amid the coronavirus pandemic, many schools around the world were forced to close or move to alternate instruction and gathering people together in a community became difficult. Within this context, we, along with other educators and practitioners, adapted our restorative justice methodologies to virtual spaces. In this chapter, we explore the potential of virtual restorative justice with a comparison to current literature on its in-person practice, as well as the concrete experience and application amid the coronavirus pandemic. First, we highlight key elements and assumptions about restorative justice that are rooted in in-person interactions. We then demonstrate how this could be adapted to online environments by describing what virtual restorative practices look like. We draw on and extend current literature, presenting a limited review of academic sources before the pandemic and popular media discussing virtual adaptations during 2020. We next detail our own involvement in processes of adapting restorative practices to virtual spaces in schools and communities during the pandemic. The data from this section comes from our own experience as practitioners, as well as work evaluating implementation in school settings. Finally, we end by highlighting opportunities, challenges, and questions to be addressed in considering the potential of virtual spaces for practices of restorative justice.